A new species of the Arthuri Complex of the Strodei Subgroup of Nyssorhynchus (Diptera: Culicidae) - Sant’ana, Denise Cristina; Sallum, Maria Anice Mureb (Zootaxa, 2022)
Nyssorhynchus (Nyssorhynchus) rondoniensis, a new species of the Arthuri Complex of the Strodei Subgroup, is described and validated using morphological characters of the adult male and female, male genitalia, fourth-instar larva and pupa. The new species is recorded in the municipalities of Campo Novo de Rondônia and Monte Negro, Rondônia State, Brazil. Based on DNA sequence data, the new species (as Ny. arthuri species C) was found to belong to a separate lineage within the Arthuri Complex. Morphological characteristics of the male genitalia and fourth-instar larva confirmed that the new species shared morphological similarities with other species of the Arthuri Complex, but it can be distinguished by characteristics of the male genitalia, adult female and larva. Nyssorhynchus rondoniensis may be involved in malaria transmission because females can be easily misidentified as Ny. oswaldoi (Peryassú, 1922) s.l. or Ny. konderi (Galvão & Damasceno, 1942) s.l. Both species were previously hypothesized to be local vectors in Acre and Rondônia States.